Effect of Dimensions of Workplace Spiritualism: Meaningful Work, Sense of Community, Organizational Values and Compassion with Reference to Job Satisfaction - Sapra, Jayashree; Mathur, Ishita (SAINTIS Publishing, 2020)
Workplace spiritualism (WS), although a newer concept, is seen to have gained tremendous importance in the recent years and is expected to furthermore expand in scope and applicability in future The objective of this research paper is to understand the impact of workplace spiritualism on the degree of job satisfaction of employees with special reference to IT industry. Through this research impact of Workplace Spiritualism on enhancing employee performance was studied. The methodology used was articulating the problem, formulating the hypothesis and collection of facts from survey. An empirical study was carried out to get the results for this research study. A total of 110 completed questionnaires were received. Descriptive Statistics, casual research and correlations were carried out. Four main dimensions used for measuring the spiritualism at the workplace are identified which include meaningful work; sense of community; organizational values as well as compassion. The results of this study showed that all the four dimensions of WS have a significantly strong as well as positive relationship with the level of employee job satisfaction. Sense of community as well as organizational values are the two most important dimensions influencing job satisfaction. The paper recommends that WS should be enhanced in the IT sector since it influences job satisfaction and employee performance. The study would be useful for the policy makers, researchers and HR professionals to understand the importance of WS in IT sector.